‘I don't want her to be overweight like I was as a girl’: Mother/child bodily connections in nutritional carework - Tanner, C.; Maher, J.; Fraser, Suzanne (Routledge, 2013)
Widespread concern about a childhood obesity ‘epidemic’ has focused attention on the bodies, weight and food behaviours of mothers and their children. In childhood obesity-related discourse, mothers' bodies are framed in relation to the bodies of children, most directly in claims that fat mothers produce fat babies. Drawing on data from a qualitative study involving interviews with mothers of pre-school aged children, this paper examines how the blurring of body boundaries between women and children are translated into responsibilities in feeding. We argue that in the contemporary stigmatisation of fat, the external auditing of maternal feeding and children's bodies connects the bodies of mothers and children in detrimental ways. By focusing on the ways women are held responsible for both their own and children's bodies, we draw attention to how bodily aspirations, conflict and failure, shame, self-surveillance, judgement and guilt connect women to the bodies of their children. We stress the embodied significance of mother/child relations in early childhood nutritional care and we argue that a punitive anti-fat ethic threatens positive health outcomes for mothers and children.